Pedagogical Renewal in Portugal Between the 1950s and the 1970s: Actors, Reception of Ideas, Educational Experiences - Pintassilgo, Joaquim; de Andrade, Alda (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2020)
This article aims to reflect on the appropriations of pedagogies presented as alternatives to the so-called traditional pedagogy, in Portugal, from the 1950s to the 1970s, whilst under an authoritarian regime. Furthermore, it aims to assess the role played in this movement by a group of educators who were considered progressive. We also propose, within this framework, to think through the complexity of the relations between tradition and innovation, using the concept of “tradition of innovation” as a reference point.